Health-Seeking Behaviour and its Determinants Among Adult Population: A Comparative Study Between Urban and Rural area of Western Uttar Pradesh - Sulthana, Banisha; Gautam, Neelam S; Bano, Tanveer; Jain, Seema; Kumar, Sanjeev (Indian Journal of Community Health, 2025)
Background: Health-seeking behaviour is any remedial action adopted by an individual for his/her health issue. It is essential to know health seeking behaviour of a community and the factors affecting it in order to provide the needed health care services. Aim & Objective: To assess health-seeking behaviour and factors affecting it among adults in rural and urban areas of Meerut. To estimate their awareness about health insurance policies. Settings and Design: A cross-sectional study was conducted in rural and urban adult population of Meerut, Uttar Pradesh from 1st July to 30th September, 2023. Methods and Material: A sample size of 200 each from rural and urban areas was estimated. Selection of study participants was done by multistage sampling. A pre-designed, pre-tested and semi-structured schedule was used for data collection. Statistical analysis used: Statistical analysis was performed with Epi Info. Results: Out of 400 study subjects, positive health-seeking behaviour was shown by 91% in urban area and 60% in rural area. Majority of them preferred public health facilities in both the areas. Convenience of approach was major factor affecting health-seeking behaviour in rural, while it was low cost of treatment in urban. Most of rural adults were unaware of health insurance policies, while around half of urban adults were aware of it. Conclusions: Urban adults have better positive health seeking behaviour and awareness on health insurance policies compared to rural adults.